2023
DOI: 10.7717/peerj-cs.1673
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle target detection method based on improved YOLO V3 network model

Qirong Zhang,
Zhong Han,
Yu Zhang

Abstract: For the problem of insufficient small target detection ability of the existing network model, a vehicle target detection method based on the improved YOLO V3 network model is proposed in the article. The improvement of the algorithm model can effectively improve the detection ability of small target vehicles in aerial photography. The optimization and adjustment of the anchor box and the improvement of the network residual module have improved the small target detection effect of the algorithm. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Liu et al [11] based their model on the Faster R-CNN network, modified the anchor point size, and detected corn male tassels by replacing different backbone feature extraction networks, and they concluded that a Residual Neural Network (ResNet) is better than a Visual Geometry Group Network as a feature extraction network for corn male tassels, but a large number of parameters and FLOPs can lead to a slow detection speed in Faster R-CNN. Hongming Zhang et al [12] took maize seedlings as the target, added lightweight improvement measures, and proposed a convolutional neural network detection network for seedling acquisition, which realized the acquisition of maize seedling plants at high throughput and completed the prediction of yield assessment. Liang et al [13] applied several mainstream detection models such as Faster R-CNN [14], SSD [15], and YOLOv3 [16] to train and predict the labeled corn tassel dataset and compared the results.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [11] based their model on the Faster R-CNN network, modified the anchor point size, and detected corn male tassels by replacing different backbone feature extraction networks, and they concluded that a Residual Neural Network (ResNet) is better than a Visual Geometry Group Network as a feature extraction network for corn male tassels, but a large number of parameters and FLOPs can lead to a slow detection speed in Faster R-CNN. Hongming Zhang et al [12] took maize seedlings as the target, added lightweight improvement measures, and proposed a convolutional neural network detection network for seedling acquisition, which realized the acquisition of maize seedling plants at high throughput and completed the prediction of yield assessment. Liang et al [13] applied several mainstream detection models such as Faster R-CNN [14], SSD [15], and YOLOv3 [16] to train and predict the labeled corn tassel dataset and compared the results.…”
Section: Introductionmentioning
confidence: 99%